The role of the class council for the organization of pedagogical work - Freire de Souza Rocha, Rhaíssa Sheri (2021)
Based on the assumption that the discussions and processes in the class council interfere with the teaching practices of the teacher in the classroom, this study has the general objective of analyzing the contributions of the class council meetings to the organization of the pedagogical work. The qualitative approach research was developed through a Case Study. For data collection documentary analysis was used, observation of the class council and semi-structured interview. The findings indicate that the logic of classificatory and excluding evaluation that guides the class council influences the pedagogical work of the teacher in the classroom.